Impact of Beta Thalassemia Minor on Mineral Homeostasis: A Comprehensive Analysis - Ihsan Mardan Al-Badran; Zainab A. Almnaseer; Amani Naama Mohammed; Hamid Jaddoa Abbas (International Journal of Medical Toxicology and Legal Medicine, 2025)
This paper aims to identify hypomineralization in patients with beta-thalassemia minor through an analysis of serum calcium, iron, magnesium, phosphorus, copper, and zinc concentrations in a series of patient subpopulations. In the 50 subjects studied, mineral concentration differences between clusters were assessed by Welch's ANOVA with Games-Howell post hoc tests. K-means clustering and principal component analysis were performed to identify and visualize the biochemical profiles of mineral intercorrelations via Pearson correlation analysis. The results showed significant variations in mineral concentrations between clusters. Calcium levels averaged 8.31 mg/dL in the cohort, with deficiencies noted in Cluster 2, which had a mean of 7.7 mg/dL. Iron levels varied significantly: Cluster 0 indicated chronic iron overload with a mean of 304.0 µg/dL, while Cluster 2 exhibited lower levels with a mean of 96.8 µg/dL. Magnesium concentrations were generally normal; however, Cluster 3 showed mild deficiencies (mean: 2.23 mg/dL), suggesting susceptibility to oxidative stress. Increased phosphorus levels were observed (mean: 5.1 mg/dL), while copper concentrations were highest in Cluster 1 (mean: 164.2 µg/dL) and zinc levels were lowest in Cluster 3 (mean: 81.2 µg/dL), reinforcing the need for individualized supplementation programs. The Pearson correlation showed moderate positive correlations between calcium and magnesium (p < 0.01) and between copper and zinc (p < 0.05), indicating potential interrelationships among these essential minerals.